ELECTRONICS IN ACCOUNTING. - Matz, Adolph (The Accounting Review, 1946)
Abstract Man's desire to create some mechanical means for aiding him in carrying out simple arithmetic processes dates back to very early times. Computing machines are not a product of this century. Most modern mechanical calculating machines have really nothing basic in them. Of course, many refinements have been introduced but the fundamental idea was never changed. However, these machines were not used and known very widely as it was still impossible to duplicate parts and still achieve reliable results as is now done by modern processes of fabrication. When the modern tabulating machine with its punch card was introduced, it had a tremendous influence upon business and financial procedure. If, today, reliance still had to be placed on long-hand methods, the scope and complexity of present-day business problems would be practically impossible. This new arithmetical technique has been so widely adopted that over 10,000 tons of punch cards are used each year in the U.S. Refinements in the punched-card method have included use of electrical contacts through the holes instead of mechanical connections.